ANALISIS KECEMASAN MATEMATIKA PADA SISWA KELAS IV SDN 2 SUKATANI - Tryana Rahayu, Diena; Alani, Nabella; Ratiana, Sagita; Cikal Putri, Aulia Sunarti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the level of mathematics anxiety among fourth-grade students at SDN 2 Sukatani. Mathematics anxiety is an emotional condition characterized by feelings of fear, tension, and worry when dealing with mathematics learning, which can affect students' learning outcomes. This research employed a descriptive quantitative approach with a survey method. The sample consisted of 16 students selected using total sampling technique. The instrument used was a mathematics anxiety questionnaire consisting of 25 valid statements based on somatic and attitude indicators. Data analysis was conducted descriptively by calculating scores and percentages to classify anxiety levels into low, moderate, and high categories. The results showed that 37.5% of students were in the high anxiety category, 25% in the moderate category, and 37.5% in the low category. These findings indicate that students' mathematics anxiety levels vary and require attention in the learning process. Therefore, teachers are expected to create a comfortable and enjoyable learning environment to reduce students' anxiety.